Antifungal Potential of Garcinia parvifolia (miq.) miq. Stem Bark Extract - Lely Salmitha; Suhartini Suhartini; Nurhikmah Nurhikmah (Jurnal Ners, 2025)
The use of natural plant products that are effective against many pathogenic fungi in humans is one way to avoid fungal infections and reduce the impact of resistance caused by synthetic drugs. The plant Garcinia parvifolia (Miq.) Miq. is empirically utilized by the local community as a medicinal plant. One of them is by the Mului community, who use it as a remedy for athlete's foot caused by Candida albicans. This research aims to measure the antifungal activity of the Stem Bark Extract of G. parvifolia (Miq.) Miq. The extraction was carried out using three different solvents: Methanol, Ethyl Acetate, and n-hexane. The three types of extracts were then tested for their ability to inhibit the growth of C. albicans. The antifungal activity test results of the three G. parvifolia (Miq.) Miq. extracts showed that G. parvifolia (Miq.) Miq. can potentially be developed into a medicinal ingredient for treating C. albicans infections. It was found that extraction with ethyl acetate solvent has a powerful ability to inhibit the growth of C. albicans at four different concentrations. Therefore, using ethyl acetate solvent in the extraction process can be an appropriate method for extracting G. parvifolia (Miq.) Miq.